The Effect of Marketing Mix (4p) on Perceived Value, Trust, Purchase, and Repurchase Decisions Using SEM Tools - Sajidah Tiara Ayu Wiranda; Minto Waluyo (Indonesian Interdisciplinary Journal of Sharia Economics)
The rapidly evolving business landscape, particularly in manufacturing and service sectors, demands effective marketing strategies to secure a competitive edge and sustain market presence. This paper focuses on the chemical industry, exemplified by CV Rizqy Anhu Kemala, which faces challenges such as product quality dissatisfaction and increased competition. The study explores the impact of the 4P marketing mix—Product, Price, Promotion, Place—on perceived consumer value, trust, and repurchasing decisions. By collecting questionnaire data and applying Structural Equation Modeling (SEM), the research aims to provide insights. The findings show that the relationship between the independent variable product (X1) has a positive effect on perceived value, price (X2) does not have a positive effect on perceived value, promotion (X3) and location (X4) cannot be proven because these variables are excluded. While the perceived value attachment variable (Y) has a positive and significant effect on trust.